A Multidisciplinary Approach for the Archaeometric Study of Pozzolanic Aggregate in Roman Mortars: The Case of Villa dei Quintili (Rome, Italy). (28th February 2014) - Belfiore, C. M.; Fichera, G. V.; La Russa, M. F.; Pezzino, A.; Ruffolo, S. A.; Galli, G.; Barca, D.
Abstract : This contribution focuses on the study of historical mortars from a Roman archaeological site known as Villa dei Quintili, a monumental villa located in the south‐eastern part of Rome (Italy). The study was carried out on 38 mortar samples, collected from several edifices within the complex. A multi‐analytical approach, including polarized optical microscopy, scanning electron microscopy coupled with energy‐dispersive system and laser ablation inductively coupled plasma mass spectrometry, was used to analyse the pozzolanic material used for the preparation of mortars. Data obtained on both major and trace elements were compared with the compositions of Pozzolana Rossa, Pozzolana Nera and Pozzolanella samples from the Alban Hills volcanic district, collected from a historic quarry nearby, as well as with literature data. The results of such a multidisciplinary approach allowed us to recognize the use of all three pozzolan types for the aggregate fraction of examined mortars from the Villa dei Quintili .